2016
DOI: 10.1007/s10826-016-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting and Emerging Adult Self-Efficacy: Implications for Mental and Physical Health

Abstract: Helicopter parenting has become an increasing concern among practitioners, college administrators, and professors. Further, some research has indicated that this form of parenting may have a deleterious effect on emerging adult college students' mental health. This study examines the factor structure of the Helicopter Parenting Behaviors measure, a recent scale developed to examine intrusive and supportive parenting behaviors, by using confirmatory factor analysis. We utilized a self-determination theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
130
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 82 publications
(103 reference statements)
15
130
3
6
Order By: Relevance
“…However, only three published studies have examined potential mediators of these associations, meaning that the mechanisms by which helicopter parenting may be associated with poor mental health outcomes for college students have not been largely explored. Reed et al (2016) found that helicopter parenting and autonomy support have indirect relationships with anxiety and depression through lower selfefficacy. Schiffrin et al (2014) reported that relationships between helicopter parenting/autonomy support and depression were mediated by college students' perceived violation of their need for autonomy and competence.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, only three published studies have examined potential mediators of these associations, meaning that the mechanisms by which helicopter parenting may be associated with poor mental health outcomes for college students have not been largely explored. Reed et al (2016) found that helicopter parenting and autonomy support have indirect relationships with anxiety and depression through lower selfefficacy. Schiffrin et al (2014) reported that relationships between helicopter parenting/autonomy support and depression were mediated by college students' perceived violation of their need for autonomy and competence.…”
Section: Introductionmentioning
confidence: 98%
“…One area that has received less research atten tion (but where the literature is perhaps most consistent) concerns links between helicopter par enting behaviors and poor mental health outcomes in college students. College students who report that their parents engage in high levels of helicopter parenting endorse more symptoms of generalized anxiety (Darlow, Norvilitis, & Schuetze, 2017;Reed et al, 2016), social anxiety (Kouros, Pruitt, Ekas, Kiriaki, & Sunderland, 2017), depression (Darlow et al, 2017;Reilly & Semkovska, 2018;Schiffrin et al, 2014), as well as greater psychotropic medica tion use for anxiety and depression (LeMoyne & Buchanan, 2011). However, only three published studies have examined potential mediators of these associations, meaning that the mechanisms by which helicopter parenting may be associated with poor mental health outcomes for college students have not been largely explored.…”
Section: Introductionmentioning
confidence: 99%
“…(Darlow, Noviltis, & Schuetze, 2017;C. Han, 2016;Kouros et al, 2017;LeMoyne & Buchanan, 2011;Reed, Duncan, Lucier-Greer, Fixelle, & Ferraro, 2016;Schiffrin et al, 2014).…”
Section: (Self-determination Theory [Sdt])unclassified
“…The predominant stereotypes about the involvement of today's parents of college students depicts them as undesirable and negative (Carney-Hall, 2008;Taub, 2008). More specifically, elevated levels of parent and family involvement have been linked to emotional and psychological difficulties among college students (LeMoyne & Buchanan, 2011;Kwon, Yoo, and Gagne, 2017;Reed et al, 2016;Ulutas & Aksoy, 2014). The college enrollment options may be more limited among first-generation and students of color with strong ties to their parents and who do not want to be physically distant from family (Lopez Turley et al, 2010).…”
Section: Family Engagement In Collegementioning
confidence: 99%
“…Perhaps the most pervasive negative stereotype surrounding parent involvement is the notion of helicopter parents, also termed bulldozers, black hawk parents, and kamikaze parents (Kiyama & Harper, in press;Wartman & Savage, 2008). These terms suggest that parents' role is overly hovering, extreme, and potentially harmful to students' development (Kiyama & Harper, in press;Kwon, Yoo, & Gagne, 2017;Reed et al, 2016;Taylor, 2006. More often than not, underrepresented families are missing or portrayed as less involved, harmful, and less resourceful for their college-aged children.…”
Section: Family Engagement In Collegementioning
confidence: 99%